Perioperative management of radical cystectomy in the Nordic countries. (2nd January 2019) - Oedorf, Kimie; Skaaheim Haug, Erik; Liedberg, Fredrik; Järvinen, Riikka; Bjerggaard Jensen, J⊘rgen; Arum, Carl-J⊘rgen; Wrist Lam, Gitte
Abstract: Objective: Radical cystectomy is performed in all of the Nordic countries, but the current practice patterns remain unclear. This study explored current perioperative care and adherence to the Early Recovery After Cystectomy (ERAC) protocol and EAU guidelines by cystectomy surgeons in the Nordic countries. Materials and methods: The study was performed as a survey including 47 centers performing cystectomies in Norway, Sweden, Finland, Iceland and Denmark. The survey addressed surgical volume, complications, preoperative imaging, use of chemotherapy, multidisciplinary conferences and current practice for perioperative and postoperative care. The survey was dispersed electronically and data was collected between November 2016 and October 2017. Results: The response rate was 55%, with a 78% completion rate of the 58 main questions. Most centers performed 10–50 cystectomies annually. Of responding centers, 96% had preoperative multidisciplinary conferences. Bowel preparation was avoided in 95% of centers and 92% did not use nasogastric tubes. All centers offered neoadjuvant chemotherapy, prescribed prophylactic antibiotics, used urinary drainage and did in-department follow-up. None of the responders waited for proof of bowel function before restarting oral diet and 96% had a standard plan for early mobilization. Conclusion: This study found a high degree of implementation of ERAC and EAU guidelines and similar practice patterns regarding perioperative management of Radical cystectomy among Nordic countries.